Genetic epidemiology of BRCA1- and BRCA2-associated cancer across Latin America - Josef S. Herzog; Yanin Chavarri-Guerra; Danielle Castillo; Julio Abugattas; Cynthia Villarreal-Garza; Sharon Sand; Jessica Clague-Dehart; Rosa M. Alvarez-Gómez; Talia Wegman-Ostrosky; Alejandro Mohar; Pamela Mora; Azucena Del Toro-Valero; et al. (npj Breast Cancer, 2021)
Abstract The prevalence and contribution of BRCA1/2 (BRCA) pathogenic variants (PVs) to the cancer burden in Latin America are not well understood. This study aims to address this disparity. BRCA analyses were performed on prospectively enrolled Latin American Clinical Cancer Genomics Community Research Network participants via a combination of methods: a Hispanic Mutation Panel (HISPANEL) on MassARRAY; semiconductor sequencing; and copy number variant (CNV) detection. BRCA PV probability was calculated using BRCAPRO. Among 1,627 participants (95.2% with cancer), we detected 236 (14.5%) BRCA PVs; 160 BRCA1 (31% CNVs); 76 BRCA2 PV frequency varied by country: 26% Brazil, 9% Colombia, 13% Peru, and 17% Mexico. Recurrent PVs (seen ≥3 times), some region-specific, represented 42.8% (101/236) of PVs. There was no ClinVar entry for 14% (17/125) of unique PVs, and 57% (111/196) of unique VUS. The area under the ROC curve for BRCAPRO was 0.76. In summary, we implemented a low-cost BRCA testing strategy and documented a significant burden of non-ClinVar reported BRCA PVs among Latin Americans. There are recurrent, population-specific PVs and CNVs, and we note that the BRCAPRO mutation probability model performs adequately. This study helps address the gap in our understanding of BRCA-associated cancer in Latin America.